A neutralizing bispecific single-chain antibody against SARS-CoV-2 Omicron variant produced based on CR3022 - Yu, Kaikai; Liu, Bin; Yu, Haotian; Sun, Chengbiao; Wang, Xuefeng; Li, Guorui; Dong, Mingxin; Wang, Yan; Zhang, Jianxu; Xu, Na; Liu, Wensen (Frontiers in Cellular and Infection Microbiology, 2023)
The constantly mutating SARS-CoV-2 has been infected an increasing number of people, hence the safe and efficacious treatment are urgently needed to combat the COVID-19 pandemic. Currently, neutralizing antibodies (Nabs), targeting the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein are potentially effective therapeutics against COVID-19. As a new form of antibody, bispecific single chain antibodies (BscAbs) can be easily expressed in E. coli and exhibits broad-spectrum antiviral activity. In this study, we constructed two BscAbs 16-29, 16-3022 and three single chain variable fragments (scFv) S1-16, S2-29 and S3022 as a comparison to explore their antiviral activity against SARS-CoV-2. Our results revealed the potent neutralizing activity of two BscAbs 16-29 and 16-3022 against SARS-CoV-2 original strain and Omicron variant infection. In addition, we also found that SARS-CoV RBD-targeted scFv S3022 could play a synergistic role with other SARS-CoV-2 RBD-targeted antibodies to enhance neutralizing activity in the form of a BscAb or in cocktail therapies. Combining the advantages of cocktails and single-molecule strategies, BscAb therapy has the potential to be developed as an effective immunotherapeutic for clinical use to mitigate the ongoing pandemic.